2014
DOI: 10.1177/183335831404300104
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Quality Assurance Model (GQAM) for Successful E-Health Implementation in Rural Hospitals in South Africa

Abstract: Although e-health can potentially facilitate the management of scarce resources and improve the quality of healthcare services, implementation of e-health programs continues to fail or not fulfil expectations. A key contributor to the failure of e-health implementation in rural hospitals is poor quality management of projects. Based on a survey 35 participants from five rural hospitals in the Eastern Cape Province of South Africa, and using a qualitative case study research methodology, this article attempted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, despite the launch of many telemedicine programs in Middle Eastern countries since the 1990s (Saudi Arabia, United Arab Emirates (UAE), Iran, Turkey, Kuwait, Bahrain, Iraq, Syria, Oman, Qatar, and Jordan), the progress made in the utilization has been insufficient and varied across countries (Bali, Gupta, Khan, & Pakhare, 2016), with most telemedicine initiatives not progressing as expected (Barakat, Woolrych, Sixsmith, Kearns, & Kort, 2013;Jalghoum & Khasawneh, 2016). Poor progress may lead to failure, especially when implemented in low-income countries such as Yemen and Syria (Al-Fadhli, Othman, Rashed, & Ramasamy, 2015;Ruxwana, Herselman, & Pottas, 2014). Zayyad and Toycan (2018) suggested that the poor adoption of telemedicine services in most Middle Eastern countries can be attributed to cultural barriers (Alajlani & Clarke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, despite the launch of many telemedicine programs in Middle Eastern countries since the 1990s (Saudi Arabia, United Arab Emirates (UAE), Iran, Turkey, Kuwait, Bahrain, Iraq, Syria, Oman, Qatar, and Jordan), the progress made in the utilization has been insufficient and varied across countries (Bali, Gupta, Khan, & Pakhare, 2016), with most telemedicine initiatives not progressing as expected (Barakat, Woolrych, Sixsmith, Kearns, & Kort, 2013;Jalghoum & Khasawneh, 2016). Poor progress may lead to failure, especially when implemented in low-income countries such as Yemen and Syria (Al-Fadhli, Othman, Rashed, & Ramasamy, 2015;Ruxwana, Herselman, & Pottas, 2014). Zayyad and Toycan (2018) suggested that the poor adoption of telemedicine services in most Middle Eastern countries can be attributed to cultural barriers (Alajlani & Clarke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of critical stakeholders, user involvements, together with independent Quality Assurance Evaluations (Ruxwana et al ,. 2014).…”
Section: Independent Variablementioning
confidence: 99%
“…This section aims to choose the sources to complete searches for primary studies. First of all, we carried out preliminary searches with the intention of both identifying existing systematic reviews and assessing the volume of potentially relevant studies, so that in this case we found the following relevant initiatives: Asoh and Rivers [ 15 ], Bangert et al [ 16 ], Esteves [ 17 ], Ferrer-Roca et al [ 18 ], Gama et al [ 19 ], Golemanov et al [ 20 ], Goletsis and Chletsos [ 3 ], Gutiérrez and Riveill [ 21 ], Harris et al [ 22 ], Holbrook et al [ 23 ], Hadwich et al [ 24 ], Kastania and Kossida [ 25 ], Liu and Park [ 26 ], Monda et al [ 27 ], Moumtzoglou and Kastania [ 28 ], Palos et al [ 29 ], Pate and Turner-Ferrier [ 30 ], Ruxwana et al [ 31 ], Ferrer-Roca et al [ 18 ], Smedberg [ 32 ], Tan et al [ 33 ], and Zvikhachevskaya et al [ 34 ]. Secondly, a Web-search was performed to find out other relevant and new concepts associated with our Quality Characteristics.…”
Section: A Strategic Study For E-health Systemsmentioning
confidence: 99%